PENGARUH KAJIAN KITAB KUNING TERHADAP KETAATAN BERIBADAH IBU MUSLIMAT DI DESA PREKBUN KECAMATAN PADEMAWU - Qomariyah, Nurul; Arifa, Luluk Lusiana; Purwanto, Eko; Suhada', Haris; Qomariyah, Fitriyatul (Rabbani: Jurnal Pendidikan Agama Islam, 2022)
This paper tries to trace the study of the yellow book among muslim women which was carried out in the village of Prekbun Pademawu in the following scope: (1) the meaning of study of the yellow book for muslim mother. (2) implementation of the yellow book study in prekbun village. (3) the impact of the study of the yellow book on the observance of worship of muslim women. Thourgh a case study approach, the research reveals that the study is named Quwat (Qur’an and sholawat). Who is guided by acleric as a strengthening understanding of muslim mothers. With the study of the yellow book, the impact felt by muslim mothers is increasing devotion in worship, istiqomah in worship, ad adding to sunnah worship.